KRITIK ISLAMISASI SAINS Telaah Pemikiran Fazlur Rahman - Topik Topik (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2017)
The Islamization of science in knowledge will run smoother if Muslims are aware of and understand Islamic demands in all fields of life. The Islamization of science and knowledge does not only occur out there, but occurs in the mind through language, reason and thoughts in the human mind. So the starting point for the Islamization of science is ourselves and our understanding of Islam and its appreciation in everyday life. Meanwhile, for the success of the Islamization of science, political will is needed because it involves education which should be under the authority of the government. Al-Quran as a universal holy book will always help Islamic and non-Islamic thinkers in the development and progress of Islam in particular and the world in general, so it must be appreciated and utilized, because without intellectual thinkers the world would not have progressed until now.